Memetakan Common Method Bias (CMB) Dalam Penelitian Sosial Kuantitatif: Tinjauan Pelingkupan Terhadap Strategi Identifikasi dan Kontrol - Saptoto, Ridwan; Dima Hanif, Faiqal; Giselle Stephany Simanjuntak, Jane; Rahman Afandi, Ardian (Faculty of Psychology, Universitas Surabaya, 2026)
Cross-sectional survey is a research design widely used in Psychology. However, this method may suffer from common method bias (CMB). This study aims to identify studies on common method bias (CMB) and how to address it. A scoping review design was applied, in which eight databases (Science Direct, Springer, Sage Pub, Taylor & Francis, Directory of Open Access Journals [DOAJ], BASE, Scopus, and Web of Science) were invoked to identify interested articles based on the inclusion criteria, i.e., (a) empirical research on common method bias (CMB); (b) published in peer-reviewed English journals from 2003 to 2025; (c) open-accessed articles. Nine eligible articles were captured to be involved in the data-extraction process in parallel by authors to ensure consistency and revealed several findings. Firstly, the common method bias (CMB) impact cannot be overlooked. Next, scholars conducted procedural and statistical remedies to identify and control common method bias (CMB). This study provides insight into how to identify and control the common method bias (CMB) effect and suggests the finding to be shared in research methods courses to improve research quality. Furthermore, this study can also serve as a reference for future research in psychology that employs self-report measurement tools to identify and control common method bias (CMB), thereby ensuring more accurate research conclusions.